Teachers' narratives of professional experience: building a culture of collaborative inquiry - Moreira, Maria Alfredo (2008)
Objectives or purpose The symposium aims at presenting 3 case studies of teachers’ narratives of professional practice, undertaken within contexts of initial and specialized teacher education. The use of journals as reflective narratives of experience aims at promoting inquiry into professional practice by integrating teaching and research, individual reflection and cooperation. The authors will present the rationale, development, and results of the 3 case studies, as well as discuss the potential and constraints of this inquiry-oriented and collaborative approach to teacher development. Perspective(s) or theoretical framework Our aim as teacher educators is to articulate collaborative and critical teacher development strategies with the development of teacher inquiry and autonomy, seeking to study the role of teachers in the co-construction of pedagogical knowledge, through reflective dialogue on the participants’ personal theories on educational situations (Clandinin & Connelly, 1994; Clandinin, 1992). This orientation is associated with the intention of creating teacher and supervisor development situations that will allow (prospective and experienced) teachers to co-construct their professional knowledge in cooperation with significant others. In this way, the road to professional autonomy and emancipation is enhanced, for it becomes a collective endeavor, instead of an individual one (Moreira, Durães & Silva, 2006; Ribeiro, 2006; Melo, 2007; 2008, forthcoming). Using collaborative journals presupposes systematic regulation of the teaching and learning process, as well as the regulation of teacher education processes, so that problems and solutions, potentialities and constraints may be identified. Only then are we in a position to validate its benefits as a teacher development strategy on the road to professional autonomy. Methods, techniques, or modes of inquiry The approach to data analysis will be inductive, based on the assumptions and procedures of grounded theory (Glaser & Strauss, 1967). We will be looking at themes that arise from data, aimed at articulating perceptions of practice and espoused theories of action. The theoretical underpinnings and methodology of CDA will be also mobilized in the task of trying to uncover historical and ideological constraints on teachers’ discourse and action (Fairclough & Wodak, 1997; Gee, 1999). Data sources or evidence The main data sources are teachers’ collaborative journals, undertaken within three teacher education courses: initial education of kindergarten teachers, and two Masters’ courses on Pedagogical Supervision. Results, conclusions, and/or points of view Writing a collaborative journal allows the participants to deepen their understanding of vicarious experience and of the process of knowledge production in professional contexts, for it involves writing about feelings and emotions, as well as about thoughts and actions. It allows teachers to dive into the complexities of practice, describe it, confront their perceptions with significant others’ and reconstruct their theories of practice. Besides creating a common space where the I meets the Other, raises awareness of oneself and of situational constraints and thus feels empowered, collaborative journal writing also creates a space for a conversation in which questions are asked, contradictions are exposed, and no definite solutions are reached (Carroll & Cotterall 2007; Moreira & Ribeiro, forthcoming).